FAKTA-FAKTA SISA MAKANAN (FOOD WASTE) DI HOTEL BINTANG 3 DAN BINTANG 4 DI MAKASSAR - Darmayasa; Pastini, Ni Wayan; Nurgaha, Putu Ari; Ab, Ernawati (JURNAL BISNIS HOSPITALITI, 2024)
Food waste is one of the most pressing environmental and economic issues in the hospitality sector, particularly in 3-star and 4-star hotels. This study aims to explore the factors contributing to food waste and the strategies used to address it in 3-star and 4-star hotels in Makassar. The research employed a qualitative descriptive approach, collecting data through direct observation, in-depth interviews with hotel management, restaurant staff, and guests. The findings revealed that the main causes of food waste include guests' habit of taking excessive portions, a lack of awareness of environmental impacts, and insufficiently strict hotel policies on waste management. Some hotels have implemented efforts to reduce food waste, such as guest education, posting written reminders, and managing leftover food. However, these strategies still face several challenges, including guest resistance and management concerns about hotel image. This study suggests the need for more systematic and collaborative policies between guests, staff, and management to achieve more effective and sustainable food waste reduction.